A Sustainable Approach to Marketable Banking Stress and Burnout - Miranda, José (2023)
It is now widely acknowledged that working in marketable banking (MB) can be a major source of stress. Meeting overly ambitious commercial targets or adapting to changes in the industry can often result in stressful situations within MB. The banking industry is known for being one of the most stressful industries to work in, as evidenced by extensive research on the topic spanning several decades. Managing stress levels and preventing burnout among MB employees is crucial to improve the overall performance of the system. Using a mathematical logic-entropic approach to knowledge representation and reasoning, it is possible to assess stress levels and predict future trends, which can inform preventive and corrective actions. This may involve setting more realistic financial goals, reducing workloads, strengthening social support between employees and supervisors, and developing strategies to generate positive feedback. By effectively managing stress and burnout, the risk can be reduced, and the overall performance of MB can be improved.